Nutrient cycling in Eucalyptus dunnii Maiden: litterfall and macronutrient return in Pampa biome - Garlet, Claudinei; Schumacher, Mauro Valdir; Dick, Grasiele; Viera, Márcio (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The litterfall represents a compartment of extreme importance in the nutritional dynamics of forest ecosystems, acting as an agent regulating the processes of inputs and outputs of the mineral and organic elements at the soil-plant interface. The objective of this work was to characterize litterfall and the return of macronutrients to a five - year - old Eucalyptus dunnii stand in Pampa biome region of Alegrete, Rio Grande do Sul state, Brazil. For this, four plots of 20 m x 21 m were installed, each of which had four area collectors with 0.5 m2. In addition, within each plot four areas of 7.0 m2 were collected for collection of branches (diameter > 0.51 cm). The litter samples were collected biweekly and separated into leaf, miscellaneous, twigs (diameter < 0.5 cm) and branches fractions, then dried in greenhouses, weighed, milled and subjected to chemical analysis. The total litterfall was 9.6 Mg ha-1, in which the leaf fraction was the largest constituent (52.7% of the total). The amounts of Ca, N, K, Mg, S and P in litterfall were 109.36; 59.62; 33.99; 21.17; 5,41 and 3.93 kg ha-1, respectively, of which 72.4% of the total was represented by the sum of Ca + N. Therefore, the litterfall of this stand acts in the maintenance of soil fertility, which is important, since it is not a natural environment.